Enablers that Aid in Retention of Millennial Workforce - Anitha, J (Ushus Journal of Business Management, 2015)
Owing to revolution in smart technologies, drastic socio-cultural and political events, dynamic economic conditions, unpredicted catastrophic events, sophisticatedparental upbringing, get-now attitude, entertainment-oriented lifestyle and opportunities for challenging cum lucrative jobs have driven the organisations to face aformidable task of retaining Generation Y workforce. It has become obligatory to understand the nature of millennials as they are becoming a dominant workforceand potential leaders in an organisation. In this Volatility, Uncertainty, Complexity and Ambiguity (VUCA) situation, organisations are in dire need to propound retention strategies in managing the energetic younger workforce. This paper identifies the significant enablersnamely mentoring, job satisfaction, work environment, social consciousness, technology savviness and team work for a millennial to stay in a particular enterprise.The study is descriptive and causal, comprising data of 100 Gen Y employees confined to Coimbatore city in IT and manufacturing sectors. Descriptive statistics, ANOVA and regression were examined for the analysis of the study. The findings of the study reveals that technology savviness and team work were found to be the important enablers for retention of Gen Y and there exists a significant difference in the perception of Gen Y employees in terms of designation. Therefore organisations have to contribute viability in technological support and a collaborative workplace for teams.